Pengaruh Dukungan Sosial Terhadap Kepatuhan Pengobatan dan Kualitas Hidup Pasien dengan Penyakit Ginjal Kronis Tahun 2024 - Achmad Fauzi; Megawarni Antonia Napitupulu; Zulan Sari; Zul Qaedah Atthahirah (Jurnal Ners, 2025)
Chronic Kidney Disease (CKD) is a condition characterized by a significant and gradual decline in kidney function over a long period. Social support is crucial for CKD patients as their physical and mental conditions tend to deteriorate compared to when they were healthy. A lack of social support impacts patient compliance in undergoing hemodialysis (HD). Besides treatment compliance, the quality of life of CKD patients must also be considered. Many CKD patients feel fearful of undergoing hemodialysis therapy due to the lifelong dependency it entails. To determine the influence of social support on treatment compliance and quality of life in patients with Chronic Kidney Disease. This study used a quantitative research type and a “Quasi Experimental Pre-Post Test” design. The sample size was calculated using the Slovin’s formula. Statistical test methods included univariate tests, normality tests, and the Wilcoxon test. There is an influence of social support on treatment compliance and quality of life in patients with Chronic Kidney Disease, with p-values of 0.028 and 0.001 < 0.005, respectively. The research conducted found that social support influences treatment compliance and quality of life in patients with Chronic Kidney Disease. It is evident that there is a significant impact of social support on treatment compliance and quality of life before and after intervention. Additionally, it was found that the majority of respondents were young adults aged 40 – 59 years, predominantly male, and most respondents were employed.